Materi Khitan sebagai Sarana Pendidikan Seks pada Mata Pelajaran Fikih MI - Fatiya Sakinah; Rahma Annisa; Rahmah Desfitria; Winda Nur Febrianti; Andi Prastowo (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2021)
Islam is a religion that always teaches cleanliness. In a saying, Rasulullah SAW stated: